Mass Loss From Calving in Himalayan Proglacial Lakes - Watson, C. Scott; Kargel, Jeffrey S.; Shugar, Dan H.; Haritashya, Umesh K.; Schiassi, Enrico; Furfaro, Roberto (Frontiers in Earth Science, 2020)
The formation and expansion of Himalayan glacial lakes has implications for glacier dynamics, mass balance, and glacial lake outburst floods. Subaerial and subaqueous calving is an important component of glacier mass loss but they have been difficult to track due to spatio-temporal resolution limitations in remote sensing data and few field observations. In this study, we used near-daily 3 m resolution PlanetScope imagery in conjunction with an uncrewed aerial vehicle (UAV) survey to quantify calving events and derive an empirical area-volume relationship to estimate calved glacier volume from planimetric iceberg areas. A calving event at Thulagi Glacier in 2017 was observed by satellite from before and during the event to nearly complete melting of the icebergs, and was observed in situ midway through the melting period, thus giving insights into the melting processes. In situ measurements of Thulagi Lake’s surface and water column indicate that daytime sunlight absorption heats mainly just the top metre of water, but this heat is efficiently mixed downward through the top tens of metres due to forced convection by wind-blown icebergs; this heat then is retained by the lake and is available to melt the icebergs. Using satellite data we assess seasonal glacier velocities, lake thermal regime, and glacier surface elevation change for Thulagi, Lower Barun, and Lhotse Shar glaciers and their associated lakes. The data reveal widely varying trends, likely signifying divergent future evolution. Glacier velocities derived from 1960/70s declassified Corona satellite imagery revealed evidence of glacier deceleration for Thulagi and Lhotse Shar glaciers, but acceleration at Lower Barun Glacier following lake development. We used published modelled ice thickness data to show that upon reaching their maximum extents, Imja, Lower Barun, and Thulagi lakes will contain, respectively, about 90×106 m3, 62×106 m3, and 5×106 m3 of additional water compared to their 2018 volumes. Understanding lake–glacier interactions is essential to predict future glacier mass loss, lake formation, and associated hazards.